Механізми забезпечення якості шкільної освіти в Норвегії - Оржеховська, Олена (Studies in Comparative Education, 2013)
У статті розглянуто деякі механізми забезпечення якості шкільної освіти в Норвегії: як складові Національної системи оцінки якості, так і ті, що не є елементами системи. Висвітлено наступність і безперервність системи забезпечення якості освіти – загальний навчальний план та відповідну законодавчу базу; проаналізовано систему підготовки та оцінки роботи вчителів. В статье рассматриваются некоторые механизмы обеспечения качества школьного образования в Норвегии: как составляющие Национальной системи оценки качества так и те, которые не являются элементами системи. Статья освещает преемственность и непрерывности обеспечения качества образования – общий учебный план и соответствующую законодательную базу, анализирует систему подготовки и оценки работы учителей. The article highlights some of the mechanisms for quality school education provision in Norway: the National Quality Assessment System components and non-system ones. At the state school level there has been an introduction of a national program for after-school activities, lowering the school starting age to six years, three-year upper secondary education for all and a pedagogically more coherent educational system. The article analyzes the consistency and continuity of quality assurance provision – the general part of the curriculum and the respective legislation, the systems for preparing and assessing teachers. The aims for secondary education have been identified being the partnership with parents, finding better understanding with them, cultivating in learners Christian and humanistic values, developing them both physically and spiritually, as well as providing students with quality education. The common core of the curriculum assures consistency, continuity and life-long education, which are the guarantors of quality. The ideas of humanism are the foundation of the National Curriculum. It aims at personal development, good test results, students’ discipline, consistency, high educational standards. The current Curriculum is one of the phases of raising quality of secondary education through introduction of the outcome-based learning. Curriculum embraces the entire system of school education, including four key elements: The Core Curriculum; рамку для The Quality Framework; The subject curricula as well as the Framework for subject hours distribution. The National curriculum has also set new attainment target for students which, in its turn, required better teaching as well. To ensure students reaching attainment targets for each subject, the four – year Skills (competences) for Quality project for teachers was introduced in Norway in 1996. The project was meant to provide novice teachers with additional methodological assistance. It is highlighted in the article that the state has always considerably financed education especially post graduate and continuous education for teachers through the system of on-going educators’ professional development. Norwegian experience in organizing work in rural schools has been analyzed to be further considered for practicing in small rural school settings in Ukraine. Another important feature distinguishing Norwegian system for improving quality of school education has been identified which is cross sector cooperation to ensure quality professional development for school teachers and school administration. The GNIST project has been studied to identify ways in which Norwegian government encourages interest to the teaching profession.